Unpacking hegemonic masculinity behavioral patterns among vocational and technical high school students through teachers' lenses - Gözde Partal; Özgür Partal; Güçlü Şekercioğlu; Berker Kurt; Ümit Yıldız; Ersen Vural; Başak Eda Hancı-Azizoğlu; Hüseyin Kafes (Acta Psychologica)
Hegemonic masculinity (HM) is a global phenomenon influencing adolescent identity formation, particularly in male-dominated vocational and technical education. This mixed-methods study with a sequential explanatory design investigates manifestations of HM among male students in three Turkish vocational and technical high schools (VTHSs), combining 6 hours/week of structured observations (N = 130 students; 21-behavior checklist) with semi-structured teacher interviews (n = 15). Analysis of quantitative data (κ = 0.83; inter-rater reliability) revealed verbal as the most prevalent HM behavior HM (38.1 % of cases), followed by physical aggression (37.3 %). Qualitative analysis identified underreported HM behaviors (e.g., sexual jokes, homophobic slurs, peer intimidation), with hitting as the dominant physical aggression form and extortion as the primary coercive control tactic. Triangulation revealed teachers tacitly endorsed observed HM behaviors as ‘normal,’ underscoring institutional complicity. This study extends literature by exposing how material practices (e.g., tool rituals) reinforce HM in non-Western VTHSs—a mechanism overlooked in prior research. Implications include HM-deconstructing teacher trainings and workshop curricula redesign to disrupt patriarchal cycles.